Using spatial filters to study regional reorganization of brain connectivity in familial early onset AD (PSEN1 E280A) (2020)
ABSTRACT: Background: The most common cause of familial early onset Alzheimer Disease (AD)are the PSEN1 mutations. One of the largest family carriers of the mutation lives inAntioquia, Colombia. The study of mutation carriers provides a unique opportunityto characterize the preclinical changes and the brain reorganization strategies associ-ated with predisposition to AD. The Electroencephalography (EEG) has an enormouspotential to study the neurophysiological changes in neurodegenerative processeswith promising clinical applications. During the 2012 – 2019 period different studieson a large database of high-density EEG from PSEN1 E280A carriers were done tryingto identify early changes that could be preclinical biomarkers of ADMethod: A sample of 83 participants, belonging to families with genetic risk for AD byPSEN1 E280A mutation was included. They were distributed in three groups; asymp-tomatic carriers (AC, n=27), asymptomatic non-carriers (ANC, n=33) and a symp-tomatic group with Mild Cognitive Impairment (SYMP, n=23). We used a 60 channelEEG for recording the brain electrical activity. The relative power values were obtainedusing Matlab’s chronux toolbox. The results obtained using a workflow based on Inde-pendent Component Analysis (ICA), introduced to improve the spatial resolution givenby EEG, are discussed. A two-parameter non-parametric T-test was used to calculatethe statistical significance of the relative power among the populations analyzed.Result: The comparison of carriers of PSEN1 E280A mutation and non-carriers, showaltered brain function even in asymptomatic stage complementing previous find-ings using functional Magnetic Resonance Imaging or Positron Emission Tomography.Regions, like the Precuneus, can be screened across the neurodegenerative process,offering new potential biomarkers of AD. The multivariate analysis of brain sourcesshow generalized impairment in the brain connectivity for asymptomatic subjects. Theresults found using the workflow were compared with alternatives approaches of anal-ysis, based on scalp EEG or data obtained through inverse solution methods, corrobo-rating the findings.